2018
DOI: 10.2174/1874303x01811010046
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Tumor Necrosis Factor-α and Transforming Growth Factor-β in Prostatic Tissue are Risk Factors for Lower Urinary Tract Symptoms after Transurethral Resection of the Prostate in Benign Prostatic Hyperplasia Patients with Urinary Retention

Abstract: Background: Lower Urinary Tract Symptoms (LUTS) after Transurethral Resection of the Prostate (TURP) occur in one-third of Benign Prostatic Hyperplasia (BPH) patients, may be caused by persistent prostatic inflammation and fibrosis. Objective: This study aims to evaluate the role of inflammation and fibrosis in pathological mechanism of LUTS among patients with BPH who underwent TURP by assessing their PSA, TNF-α, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Milonas et al 17 reported that the growth of the prostate gland could be predicted based on the PSA level. Duarsa et al 6 previously found that high PSA level (>4 ng/mL) promoted LUTS and prostate volume.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Milonas et al 17 reported that the growth of the prostate gland could be predicted based on the PSA level. Duarsa et al 6 previously found that high PSA level (>4 ng/mL) promoted LUTS and prostate volume.…”
Section: Discussionmentioning
confidence: 95%
“…The active form of this hormone, dihydrotestosterone, activated androgen receptor, and promoted prostate development. 6 Prostate-specific antigen (PSA), as a marker produced by prostate's epithelial cells, should be strongly related to the increased volume of BPH. Aging showed an increasing transitional volume of the prostate with an unknown direct mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…Previous study conducted by Duarsa et al. [ 39 ] in 2018 showed a significant difference of TNF-α expression in LUTS patients after being performed a TURP compared to non-LUTS patients. In this study, we examine the association of the cytokine with prostate volume resulting in a Bivariate analysis (r=−0.089; p =0.423) and total effect analysis (r=0.010; p =0.942).…”
Section: Discussionmentioning
confidence: 96%
“…The same study conducted by Duarsa et al. [ 39 ] also evaluated the association of TGF-β which is shown to be significantly higher on BPH patients with LUTS after TURP. In the human body, TGF-β is able to induce proliferation in prostatic stromal cells, however it is also responsible in the pathway of growth arrest of the cells.…”
Section: Discussionmentioning
confidence: 99%
“…7 Nevertheless, 33-35% of patients with benign prostate enlargement with retention, have a chance to LUTS after TURP surgery, especially 2-6 weeks after surgery. 8 Several techniques have been developed, including the use of bipolar TURP (B-TURP) which is a rival to monopolar TURP (M-TURP) as conventional ones as well as the gold standard of prostate surgery therapy. In a multicenter study in Canada, which compared the impact of B-TURP and M-TURP, there were no significant differences in terms of duration of surgery and length of resection, where "functional outcome" increased significantly in both types of action.…”
Section: Introductionmentioning
confidence: 99%